Wavelet methods for Ground Penetrating Radar imaging - Liu, Fengshan; Ling, Yi; Xia, Xianggen; Shi, Xiquan (Journal of computational and applied mathematics, 2004)
A new algorithm for fixed-offset Ground Penetrating Radar imaging is derived. The forward model of this inversion scheme is based on the Born approximation and the dyadic Green function for a two-layer medium. The forward model is inverted using the Wavelet Galerkin Algorithms for solving integral equations. We use the Laplacian operator to regularize the ill-posedness of the inverse problem. Numerical results are provided to illustrate performance of the inversion scheme.